Hydroxychloroquine (HCQ) Treatment for Hospitalized Patients with COVID- 19 - Tsanovska, Hristina; Simova, Iana; Genov, Vladislav; Kundurzhiev, Todor; Krasnaliev, Jordan; Kornovski, Vladimir; Dimitrov, Nikolai; Vekov, Toni (Infectious Disorders - Drug Targets, 2022)
Objective: Studies have indicated that hydroxychloroquine (HCQ) exerts antiviral effects against SARS-CoV-2 in vitro. However, trials regarding its effects on patients are very controversial. This study aims to evaluate the efficacy of (HCQ) in the treatment of hospitalized patients with COVID-19. Methods: We prospectively enrolled 260 patients hospitalized for COVID-19 in Heart and Brain Center of Excellence- Pleven, Bulgaria, for the period from November 6 to December 28, 2020. This study is not randomized, which we compensated for with Propensity Score Matching. Patients in the HCQ group were given HCQ 200 mg 3 times a day (600mg daily) for the duration of their hospitalization plus conventional treatment, while those in the control group were given conventional treatment only. The primary endpoints were transferred to the intensive care unit, needed for mechanical ventilation, and in-hospital death. Results: Of the 260 COVID-19 patients, 178 (68.5%) were male and the mean age was of 63.78 ± 12.45 years, with the most prevalent comorbidity hypertension (68.5%). We had two subgroups: treated with HCQ and conventional treatment (128 patients) and treated with conventional treatment only (132 patients). In the primary analysis, patients in the HCQ group presented with fewer comorbidities and were younger than the group without HCQ. Patients treated with HCQ demonstrated a significant benefit in the primary endpoints compared to those without HCQ, namely, transferred to ICU – 20 (20,8%) vs. 41 (36.9%), p=0.011, need for mechanical ventilation 13 (13.4%) vs. 33 (28.2%), p=0.009 and in-hospital death 14 (10.9%) vs. 35 (26.5%), p=0,001, respectively. We repeated this analysis with PSM, where 70 matched pairs were identified. Regarding the primary endpoints, we found again a statistically significant difference between the groups. Comparing transferring to ICU, better outcomes were presented in the HCQ group: 8 (17.4%) vs. 27 (44.3%), with p= 0.003. Besides, a smaller proportion of the patients needed mechanical ventilation: 6 (12.8%), compared to the control group, 23 (35.4%), p= 0.007. Notably, patients from the HCQ group died during hospitalization: 8 (11.4%) in comparison with 19 (27.1%) from the control group, p= 0.018. Conclusion: Patients treated with HCQ demonstrated a significant benefit in the primary endpoints in our study, namely, transfer to the intensive care unit, need for mechanical ventilation, and in-hospital death. HCQ improves prognosis in hospitalized patients with COVID-19.
Keywords: heart and brain